Online Information Media To Educate Farmers With The Go-Online Farmers Program Using The Participatory Rural Appraisal (PRA) Method - Giandari Maulani, Untung Rahardja, Marviola Hardini, Ria Dwi I’zzaty, Qurotul Aini (International Journal of Advanced Science and Technology, 2020)
The Jakarta-Indonesia Ministry of Communication and Information Technology created the Digital-Based Community Economy program, which was named "The Go-Online Farmers Program” which aims to expand market access and improve the class of farmers. The Go-Online Farmers Program itself is a collaboration program of the Ministry of Communication and Information with a number of digital Business Starters (Startups) that create various mobile-based applications that aim to increase productivity in agriculture and improve the living standards of farmers and open up opportunities to improve their economies. The problem is that since the launch of The Go-Online Farmers Program, the delivery of information is only in the form of presentation slides and there are still many farmers who are not familiar with The Go-Online Farmers Program. In this study the methods used are: The Participatory Rural Appraisal (PRA) Method and the Media Production Concept (MPC) which includes Pre Production, Production and Post Production. The results of this study are an Online Information Media to educate farmers with The Go-Online Farmers Program using the PRA method in the form of Motion Graphic-based Video Socialization so that it attracts the attention and helps farmers in buying and selling online. The conclusion of this research is the need for a strategy to disseminate The Go-Online Farmers Program to farmers and the strategy of using the results of this study which has been uploaded to the YouTube channel so that information can be spread, easily accepted and disseminated to villages in Indonesia.